Diálogo y sexualidad integral en los padres de familia de octavo de básica en la Unidad Educativa Cicalpa - Salguero Castañeda, Jhosselyn Mishell (2025)
This research addressed the issue of the limited dialogue on comprehensive sexuality between parents and their eighth-grade adolescent children at the “Unidad Educativa Cicalpa”, a situation that can create vulnerability among young people due to cultural taboos and lack of information. The main objective was to interpret the data collected by measuring the impact of interventions on this dialogue and to analyse parents' level of knowledge regarding their children's comprehensive sexuality. A qualitative methodology was used, with a non-experimental action research design of a basic, field-based, and bibliographic nature, with a descriptive and cross-sectional scope. An intentional sample of parents was selected (pedagogical workshop n=43, baseline n=17) through surveys and structured questionnaires. The central proposal consisted of the design and implementation of a sixmodule pedagogical workshop (emotions, effective communication, values, body development, affective-sexual education, and prevention of adolescent pregnancy) with participatory activities to provide parents with communication tools. The initial results showed a heterogeneous capacity for dialogue, but the post-workshop evaluation revealed high satisfaction, a majority perception of improved family communication, and strong support for the continuity of the training, demonstrating that parents valued the tools received. Although the initial dialogue capacity was inconsistent, the designed pedagogical workshop was a relevant and effective strategy that significantly strengthened parents’ communication skills, positively impacting their educational role and fostering a more trusting environment to address sexuality in an open, respectful, and responsible manner within the family nucleus.